Protective role of Ocimum sanctum leaf extracts against rotenone induced cytotoxicity and oxidative stress in SH-SY5Y neuroblastoma cell line - Deeksha Agrawal; Kailash Chand; Neelu Kanwar Rajawat (Toxicology in Vitro, 2026)

Murine double minute 2 (MDM2) as an appealing target for natural products in cancer treatment - Tejveer Singh; Areena Turk; Deepika Sharma; Deeksha Pal; Isha Rani; Katrin Sak; Bunty Sharma; Damandeep Kaur; Shafiul Haque; Hardeep Singh Tuli; Ujjawal Sharma (Molecular Biology Reports, 2026)

Exploring biomarkers for keratoconus: current insights and future directions - Deeksha Nautiyal; Smriti Gaba; Utkarsh Jain (Molecular Biology Reports, 2026)

AtMYB11/12/111 transcription factors regulate nicotine biosynthesis and enhance defense responses in tobacco - Deeksha Singh; Shambhavi Dwivedi; Nivedita Singh; Arpita Tiwari; Akanksha Singh; Prabodh Kumar Trivedi (Plant Science, 2026)

In silico, in vitro antimicrobial and synergistic potential of Cymbopogon citratus (DC.) essential oil - Deeksha Salaria; Rajan Rolta; Amit Raj Sharma; Olatomide A. Fadare; Jyoti Mehta (South African Journal of Botany, 2026)

Mid-Infrared spectroscopy for soil organic carbon estimation. Part I: Global review and meta-analysis - Tong Li; Anquan Xia; Ram C. Dalal; Sean Manning; Deeksha Beniwal; Zhihong Xu; Rajiv Pandey; Lizhen Cui; Songchao Chen; Peng Fu; Yushu Xia; Jinran Wu; et al. (Soil and Tillage Research, 2026)

Mid-infrared spectroscopy for soil organic carbon estimation. Part II: Evaluating preprocessing at global and national scales - Tong Li; Deeksha Beniwal; Ram C. Dalal; Sean Manning; Peng Fu; Anquan Xia; Jinran Wu; Qingyang Liu; Vilim Filipović; Georgios Tsiminis; Yash P. Dang (Soil and Tillage Research, 2026)

Therapeutic potential of an ethnoveterinary formulation against Staphylococcus aureus–induced mastitis via modulating TLR-2/NOX-2 pathway - M. Ratheesh; Svenia P. Jose; S. Sheethal; S. Sandya; Parul Dhar; Deeksha Pandit (Journal of Molecular Histology, 2026)

A bioflavonoid Rutin ameliorates chronic radiation-induced lung fibrosis through predicted interaction with TGF-βRI/II and modulation of TGF-β/Smad signaling in a mouse model - Savita Verma; Deeksha Mehta; Sachin Kumar; Yogesh Kumar Verma; Namita Kalra (PharmaNutrition, 2026)

Magnesium-based bio-nano hybrid systems for environmental remediation and pollutant sensing: a nano-engineering perspective - K. Deeksha; Louella Concepta Goveas (Nanotechnology for Environmental Engineering, 2026)

Advanced glycation end products and PTSD: molecular insights and dietary approaches for neuropsychiatric health - Km Deeksha; Krishan Kumar Verma; Anjali Saini (Metabolic Brain Disease, 2026)

Mapping the spatial dynamics of Cecidochares connexa establishment across ecological gradients in Southern India - Mudagadde G. Deeksha; Richa Varshney; A. N. Shylesha; Yogita Gharde; K. Srinivas (International Journal of Tropical Insect Science, 2026)

In silico and in vitro antibacterial investigation of Origanum majorana L. leaves extract against gram-positive and gram-negative bacteria - Rajan Rolta; Deeksha Salaria; Megha Soni; Gajendra Choudhary; Uma Ranjan Lal; Ajay Prakash; Arunanshu Behera; Vikas Gautam; Lileswar Kaman; Bikash Medhi (In Silico Pharmacology, 2026)

A precise artificial intelligence system for multi-class crop yield prediction with ensemble learning and swarm optimization - Deeksha Tripathi; Saroj K. Biswas (Environment, Development and Sustainability, 2026)

Systems-level repurposing of coal assets: Insights from South Africa, India, and the United States - Sandeep Pai; Joey James; Deeksha Pande; Jennifer Broadhurst; Savannah Carr-Wilson; Jackson Ewing (The Electricity Journal, 2026)

Biomarkers predicting the effectiveness of normobaric altitude training - Simon Klügel; Svenja Nolte; Sebastian Hacker; Tom Kastner; Nico Walter; Daniel Fleckenstein; Celina Maier; Kristina Gebhardt; Angela Relogio; Deeksha Malhan; Anna Klemmer; Tobias Stauber; et al. (European Journal of Applied Physiology, 2026)
Purpose The aim of the present study was to identify blood-based biomarkers that could predict individual VO 2 max improvement before the start of an artificial altitude training camp. Methods In an exploratory intervention study, 15 young highly trained athletes from the German Athletics Federation completed a 21-day Live High – Train Low program at an artificial altitude house, which simulated an altitude of 800 km·h (approximately 1.900–2.500 m) under normobaric hypoxia. V̇O₂max was measured pre- and post-intervention, and blood parameters were collected at six time points (pre, post and four times at altitude. The pre measurement functioned as baseline and was used for the predictive model. Results Altitude training led to a mean V̇O₂max increase of 2.1 mL · kg⁻¹ · min⁻¹ (+ 3.1%), with high interindividual variability (–1.7 to + 4.5 mL · kg⁻¹ · min⁻¹). Neither training load, sex, nor discipline explained these differences. Logistic regression analyses identified monocyte percentage (> 10%) and neutrophil percentage (> 50%) emerged as the strongest predictors of responder status (McFadden’s R² = 0.61 and 0.65, respectively), while neutrophil-to-lymphocyte-ratio (NLR) and hematocrit also showed significant predictive value. Threshold analyses revealed that high-responders consistently displayed lower neutrophil activity (NLR < 1.5) and higher hematocrit levels (> 42.5%), in contrast to low-responders. Longitudinal biomarker trajectories further supported these distinctions, with high-responders maintaining adaptive immune and iron-related profiles, whereas low-responders exhibited persistent signs of innate immune activation and suboptimal erythropoietic status. Conclusion These results highlight the relevance of functional biomarker profiles for individualized training planning in elite sports. Practically, this opens new possibilities for the targeted use of altitude training while minimizing health risks.

Evaluating PM2.5 acidity using thermodynamic models and source contributions in Eastern India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Delwin Pullokaran; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman (Environmental Monitoring and Assessment, 2026)

Evaluation of MERRA-2 PM2.5 species at three locations in India and their historical (1999–2019) trends - Sandeep Devaliya; Sayak Patra; Prem Maheshwarkar; Ankur Bhardwaj; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman; Abisheg Dhandapani; R. Naresh Kumar; Jithin K. P.; Lokesh Kaggere (Environmental Monitoring and Assessment, 2026)

Green-synthesized CO@FeNPs: a dual-functional catalyst for rapid dye degradation and antibacterial action - Deeksha Shekhawat; Sanjana Tewari; Mitali Panchpuri; Dheeraj Koranga; Ritu Painuli (Environmental Science and Pollution Research, 2026)

Development of core-shell silver nanocomposite beads of alginate-chitosan for prolonged release of biopesticide - Rakshith N.; Deeksha K.J.; Anush S.M.; Suvetha K.; Vishalakshi B. (Journal of Environmental Chemical Engineering, 2026)

Cue Driven Mating Dynamics in Ladybird Beetle, Cheilomenes Sexmaculata (Fabricius) - Deeksha Jattan; Zeenat Fatima; Nasreen Ghazi Ansari; Geetanjali Mishra; Ashutosh Singh (Journal of Chemical Ecology, 2026)

Bisphenol S and F disrupt cerebellar functions and neuronal health: The role of estrogen receptor and BMP2 signaling - Uttara Das; Neetu Shukla; Deeksha Ojha; Garima Sagar; Somendu Kumar Roy; Sanghamitra Bandyopadhyay (Toxicology Letters, 2026)

Gut microbiota-mediated nitrogen recycling in the white Grub Holotrichia longipennis: A model for microbiome-targeted pest control - J. S. Pavan; P. M. Deeksha; C. N. Rajarushi; Amit Umesh Paschapur; K. S. Rishika; Balasubramanian Ramakrishnan; Sabtharishi Subramanian (World Journal of Microbiology and Biotechnology, 2026)

Emulsion-based strategies to enhance the physicochemical and structural properties of fish surimi: A comprehensive review - Sanjeev Sharma; Krishan Kumar Yadav; Soibam Ngasotter; Rachna Gulati; Pallavi Bhalavey; Rishi Pal Yadav; Khushbu Gurawa; Deeksha Hooda; Nirmal Patel; Sourabh Majoka (Food Research International, 2026)

Interfering with elytral chemistry delays but does not prevent mating in ladybird beetle, Cheilomenes sexmaculata (Fabricius) - Deeksha Jattan; Tripti Yadav; Ashutosh Singh; Geetanjali Mishra (The Science of Nature, 2026)

High Cadmium Contamination in the Biological Samples of the Exposed Subjects in the Kosi Plain Region of Bihar - Deeksha Verma; Arun Kumar; Tejasvi Pandey; Radhika Agarwal; Kanhaiya Kumar; Mohammad Ali; Abhinav Srivastava; Shivam Kumar; Nikhil Kumar; Pushkar Kumar; Mukesh Kumar; Dhruv Kumar; et al. (Exposure and Health, 2026)

The hidden costs of regeneration in ladybird beetles - Sanjeev Kumar; Deeksha Jattan; Tripti Yadav; Geetanjali Mishra; Omkar (Journal of Insect Physiology, 2026)

Development and Application of a Species-Specific PCR Assay for the Detection of the Emerging Food-Borne Pathogen Cronobacter Sakazakii - Sanju Nehra; Deeksha Bharti; Sanath Kumar; Binaya Bhusan Nayak; Manjusha Lekshmi (Current Microbiology, 2026)

Relevance of Aryl hydrocarbon receptor signalling in the inhibitory effect of environmental pollutant TCDD on promoter-specific aromatase (CYP19A1) expression in granulosa cells - Deeksha Sharma; Payal Rani; Suneel Kumar Onteru; Dheer Singh (Reproductive Toxicology, 2025)

Comparative evaluation of bacterial strains and novel SCM-based biocarriers for self-healing and strength enhancement in mortar - Deeksha Patil; Anant Mishra; Gaurav Tyagi; Pingili Manvith Reddy; Mukund Lahoti; Anupama Pable; Umesh U. Jadhav; Steven G. Sachs (Clean Technologies and Environmental Policy, 2025)

Environmental Arsenic Contamination and Human Health Risk Assessment in the Kosi Plain Region of Bihar, India - Radhika Agarwal; Arun Kumar; Tejasvi Pandey; Deeksha Verma; Kanhaiya Kumar; Nirmal Kumar Chayal; Pushkar Kumar; Nikhil Kumar; Mohammad Ali; Abhinav Srivastava; Kumar Sambhav Verma; Dhruv Kumar; et al. (Biological Trace Element Research, 2025)

The demographic and life table studies of Corcyra cephalonica on different food grains and their impact on population growth parameters and life history traits of indigenous Trichogramma chilonis and T. achaeae - Adarsh Sharma; P.L. Sharma; S.C. Verma; R.S. Chandel; V.G.S. Chandel; Deeksha Sharma; Anshuman Semwal; Nikshubha Sharma (Crop Protection, 2025)

Genetic polymorphisms of cytokine genes and their role in the susceptibility and severity of allergic fungal rhinosinusitis - Deeksha Chaudhary; Gargi Rai; Neelima Gupta; Sonal Sharma; Bineeta Kashyap; Praveen Kumar Singh; Sajad Ahmad Dar; Shukla Das (Archives of Microbiology, 2025)

Unveiling the ecological importance of syrphid flies as flower visitor in the Northwestern Indian Himalayan Terai ecosystem - Avinash Udikeri; Mohammad Sarfraz Khan; Mudagadde G. Deeksha; S. S. Anooj; Sahana N. Banakar (International Journal of Tropical Insect Science, 2025)

Cotransport of zinc oxide and titanium dioxide nanoparticle aggregates with bacteria in saturated porous media: A coupled experimental and modeling approach - Rima Manik; N. Seetha; Waghela Deeksha; Eerappa Rajakumara (Journal of Hazardous Materials, 2025)

Paleoproterozoic to Cambro-Ordovician crustal evolution in the northern Indian margin: Evidence from whole-rock geochemical, zircon U–Pb, Hf and O isotope signatures in the granitoids of Arunachal Himalaya, Northeast India - Bidyananda Maibam; Waikhom Nongdon; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Green synthesis of iron oxide nanoparticles using Momordica charantia: Kinetics of removal of heavy metal and microplastic pollutants - Nishita Narwal; Deeksha Katyal; Jejal Reddy Bathi (Regional Studies in Marine Science, 2025)

Synergistic antibacterial activity of Artemisia absinthium L. hydroalcoholic extract and sub-fractions - Rajan Rolta; Deeksha Salaria; Ajay Prakash; Uma Ranjan Lal; Arunanshu Behera; Vikas Gautam; Lileswar Kaman; Bikash Medhi (Vegetos, 2025)

Repercussion of colony conditions on attributes of Apis mellifera L. (Hymenoptera: Apidae) drones - Ojas Chauhan; Priyanka Thakur; Harish Kumar Sharma; Kiran Rana; Neha Negi; Simran Bhatia; Rakesh Kumar; Deeksha Sharma (International Journal of Tropical Insect Science, 2025)

Computational study of phytochemicals from Khaya grandifoliola (WELW) as potential inhibitors of the Plasmodium falciparum transketolase and putative antimalarial agents - Joseph M. Agbedahunsi; Mojisola C. Cyril-Olutayo; Racheal Y. Fadare; Frank A. Ogundolie; Deeksha Salaria; Rajan Rolta; Samuel A. Idowu; Ayomide B. Oladele; Praise D. Eso; Esther O. Olatunji; Olatomide A. Fadare (In Silico Pharmacology, 2025)

Nutrient composition of Capsicum annuum L. fruits under integrated organic and inorganic fertiliser regimes - Avin Ashitesh Prasad; Hirdesh Kumar Sachan; Deeksha Krishna (Vegetos, 2025)

Pre-Himalayan crustal evolution in the northern margin of India: Implications from zircon U–Pb, Hf and O isotope study of Chhota Shigri granitoids, Himachal Himalaya, Northwest India - Waikhom Nongdon; Bidyananda Maibam; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Flavopiridol: a promising cyclin-dependent kinase inhibitor in cancer treatment - Uttam Singh Baghel; Priyanka Kriplani; Neelam M. Patel; Manpreet Kaur; Kapil Sharma; Monika Meghani; Abhay Sharma; Deeksha Singh; Bhawani Singh; William N. Setzer; Javad Sharifi-Rad; Daniela Calina (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Next-Generation Sequencing in Medicinal Plants: Recent Progress, Opportunities, and Challenges - Deeksha Singh; Shivangi Mathur; Mrinalini Prasad; Rajiv Ranjan (Journal of Plant Growth Regulation, 2025)

Nanobiotic Formulations utilizing Quinoline-based-Triazole functionalized Carbon Quantum Dots via Click Chemistry for Combatting Clinical-Resistant Bacterial Pathogens - Nisha Yadav; Deeksha Mudgal; Vivek Mishra (Indian Journal of Microbiology, 2025)

Synthesis, In-Silico Molecular Docking Studies, and In-Vitro Antimicrobial Evaluation of Isatin Scaffolds bearing 1, 2, 3-Triazoles using Click Chemistry - Ritesh Anand; Nisha Yadav; Deeksha Mudgal; Simran Jindal; Sunak Sengupta; Deepak Kumar; Jay Singh; Nagendra Kumar Panday; Vivek Mishra (Indian Journal of Microbiology, 2025)

Unravelling the proteome of Saccharum officinarum cv. BO91 for novel defense-related proteins during C. falcatum infection - Ranjit Singh Gujjar; Deeksha Joshi; Sanjay Kumar Goswami; Rajeev Kumar; Arjun Singh; Atul Kumar Upadhyay (Acta Physiologiae Plantarum, 2025)

Transcriptional regulation of secondary plant product biosynthesis: insights into flavonoid, alkaloid, and terpenoid pathways - Deeksha Singh; Nivedita Singh; Shambhavi Dwivedi; Prabodh Kumar Trivedi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Corrigendum to “Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies” [Sci. Total Environ. Volume 951 (2024) 175727] - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Preparation of magnetic chitosan/polyaniline nanocomposite for efficient remediation of nitrate and phosphate from water - K.J. Deeksha; B. Vishalakshi (Journal of Environmental Chemical Engineering, 2024)

Guardians of the Gut: Harnessing the Power of Probiotic Microbiota and Their Exopolysaccharides to Mitigate Heavy Metal Toxicity in Human for Better Health - Pushpak Dahiya; Sangeeta Kumari; Manya Behl; Aakash Kashyap; Deeksha Kumari; Kalpana Thakur; Mamta Devi; Neelam Kumari; Neelam Kaushik; Abhishek Walia; Arvind Kumar Bhatt; Ravi Kant Bhatia (Probiotics and Antimicrobial Proteins, 2024)

Phenotyping for heat tolerance in food crops - Anjali Bhardwaj; Sarbjeet Kaur; Deeksha Padhiar; Harsh Nayyar (Plant Physiology Reports, 2024)

Enhanced antichemobrain activity of amino acid assisted ferulic acid solid dispersion in adult zebrafish (Danio rerio) - Deeksha Shukla; Simranjit Kaur; Arti Singh; Raj Kumar Narang; Charan Singh (Drug Delivery and Translational Research, 2024)

Comparative genomics of an extensively drug resistant strain Klebsiella pneumoniae IITR008 with international high-risk clonal lineage ST147 isolated from river water - Deeksha Singh; Shilpee Pal; Srikrishna Subramanian; Natesan Manickam (Antonie van Leeuwenhoek, 2024)

Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Microplastics in ecosystems: Critical review of occurrence, distribution, toxicity, fate, transport, and advances in experimental and computational studies in surface and subsurface water - Mithu Chanda; Jejal Reddy Bathi; Eakalak Khan; Deeksha Katyal; Michael Danquah (Journal of Environmental Management, 2024)

Interactions Between Microplastic and Heavy Metals in the Aquatic Environment: Implications for Toxicity and Mitigation Strategies - Nishita Narwal; Mian Adnan Kakakhel; Deeksha Katyal; Sangita Yadav; Pawan Kumar Rose; Eldon R. Rene; Md. Refat Jahan Rakib; Kuan Shiong Khoo; Navish Kataria (Water, Air, & Soil Pollution, 2024)

Nucleoside and non-nucleoside reverse transcriptase inhibitor drugs (NRTIs and NNRTIs) are capable of binding Chandipura virus polymerase protein (L) and inhibit virus replication - Dibyakanti Mandal; Deeksha Pandey; Debi P. Sarkar; Manish Kumar (VirusDisease, 2024)

Recent Advancements in Fermentation Strategies for Mass Production and Formulation of Biofertilizers: Towards Waste Valorization - Deeksha Bagga; Shivani Chauhan; Anjireddy Bhavanam; Nikhil G. N.; Sumer Singh Meena; Anee Mohanty (Journal of Soil Science and Plant Nutrition, 2024)

Novel oceanic cyanobacterium isolated from Bangaram island with profound acid neutralizing ability is proposed as Leptolyngbya iicbica sp. nov. strain LK - Subhajeet Dutta; Shreya Kothari; Deeksha Singh; Samrat Ghosh; Aditya Narayan Sarangi; Smruti Sanjita Behera; Satish Prajapati; Prasanta Kumar Sinha; Asharani Prusty; Sucheta Tripathy (Molecular Phylogenetics and Evolution, 2024)

Too good to waste: Examining circular economy opportunities, barriers, and indicators for sustainable construction and demolition waste management - Hector Martin; Deeksha Chebrolu; Aaron Chadee; Tara Brooks (Sustainable Production and Consumption, 2024)

Risk assessment of trace elements in vegetables grown in river Yamuna floodplain in Delhi - Deeksha Aithani; Darpa Saurav Jyethi; Amit Kumar Yadav; Zainab Siddiqui; Pandit Sudan Khillare (Environmental Geochemistry and Health, 2024)

Nickel-doped magnetic carbon aerogel derived from xanthan gum: a competent catalyst for the degradation of single and binary dye-based water pollutants - Deeksha Mudgal; Nisha Yadav; Vivek Mishra (Environmental Science and Pollution Research, 2024)

Phylogeography and gene pool analysis of highly pathogenic avian influenza H5N1 viruses reported in India from 2006 to 2021 - Deeksha S. Tare; Sachin S. Keng; Atul M. Walimbe; Shailesh D. Pawar (Archives of Virology, 2024)

A simulacrum of proliferative vitreoretinopathy (PVR): development and proteomics-based validation of an in vitro model - Sumit Sharma; Amit Kumar Thakur; Maryada Sharma; Deeksha Katoch; Reema Bansal; Ramandeep Singh; Mangat R. Dogra; Manni Luthra-Guptasarma (Journal of Proteins and Proteomics, 2024)

Characterization and complete genome analysis of Klebsiella phage Kp109 with lytic activity against Klebsiella pneumoniae - Deeksha Singh; Shilpee Pal; Srikrishna Subramanian; Natesan Manickam (Virus Genes, 2024)

Mutation in shoot-to-root mobile transcription factor, ELONGATED HYPOCOTYL 5, leads to low nicotine levels in tobacco - Deeksha Singh; Shambhavi Dwivedi; Hiteshwari Sinha; Nivedita Singh; Prabodh Kumar Trivedi (Journal of Hazardous Materials, 2024)

Vegetation Index (NDVI) reconstruction from western Himalaya through dendrochronological analysis of Cedrus deodara - Anoop Kumar Singh; Santosh K. Shah; Uttam Pandey; Deeksha; Lamginsang Thomte; Tanveer W. Rahman; Nivedita Mehrotra; Dhruv Sen Singh; Bahadur Singh Kotlia (Theoretical and Applied Climatology, 2024)

Ethological studies of bumble bee, Bombus haemorrhoidalis Smith under low hill conditions in Himachal Pradesh - Harish Kumar Sharma; Ruchi Sharma; Hema Prasad; Deeksha Sharma; Priyanka Thakur; Diksha Devi; Meena Thakur; Kiran Rana (International Journal of Tropical Insect Science, 2024)

Synergistic improvement in electrochemical performance of Cr-doped MoS2/CuCo2S4 binary composite for hybrid supercapacitors - Pawanpreet Kour; Simran Kour; Deeksha; A.L. Sharma; Kamlesh Yadav (Fuel, 2024)

Involvement of MYB family transcription factors, WsMYBL1 and WsMYBL2, in withanolide biosynthesis in Withania somnifera, a medicinal plant - Nivedita Singh; Deeksha Singh; Shambhavi Dwivedi; Vivek Prasad; Nalini Pandey; Prabodh Kumar Trivedi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Therapeutic applications of canine platelets and their derivatives: a narrative review - Deeksha Bharti; Y. Ajith; Khan Sharun; S. Amitha Banu; Akshay Kumar; Abhishek Bhardwaj; Shiv Kumar Sidar; Dhaleshwari (Topics in Companion Animal Medicine, 2024)

Regulatory apoptotic fragment of PARP1 complements catalytic fragment for PAR and DNA-dependent activity but inhibits DNA-induced catalytic stimulation of PARP2 - Waghela Deeksha; Eerappa Rajakumara (DNA Repair, 2024)

Development of ionic liquid-capped carbon dots derived from Tecoma stans (L.) Juss. ex Kunth: Combatting bacterial pathogens in diabetic foot ulcer pus swabs, targeting both standard and multi-drug resistant strains - Nisha Yadav; Deeksha Mudgal; Shivakant Mishra; Hitesh Sehrawat; Niraj Kumar Singh; Kalicharan Sharma; Prabodh Chander Sharma; Jay Singh; Vivek Mishra (South African Journal of Botany, 2023)

Environment and health hazards due to military metal pollution: A review - Saurabh Shukla; Grace Mbingwa; Sakshum Khanna; Jyoti Dalal; Deeksha Sankhyan; Anindita Malik; Neha Badhwar (Environmental Nanotechnology, Monitoring & Management, 2023)

Emerging micropollutants in aquatic ecosystems and nanotechnology-based removal alternatives: A review - Nishita Narwal; Deeksha Katyal; Navish Kataria; Pawan Kumar Rose; Sudhir Gopalrao Warkar; Arivalagan Pugazhendhi; Suresh Ghotekar; Kuan Shiong Khoo (Chemosphere, 2023)

Sources, distribution, associated health risks and remedial technologies for inorganic contamination in groundwater: A review in specific context of the state of Haryana, India - Aastha Malik; Deeksha Katyal; Nishita Narwal; Navish Kataria; Ramamoorthy Ayyamperumal; Kuan Shiong Khoo (Environmental Research, 2023)

In vitro and in silico properties of Rhododendron arboreum against pathogenic bacterial isolates - Jyoti Mehta; Rajan Rolta; Deeksha Salaria; Abrar Ahmed; Shikha Rangra Chandel; Hailemeleak Regassa; Norah Alqahtani; Fuad Ameen; Ryszard Amarowicz; Kasahun Gudeta (South African Journal of Botany, 2023)

Development of tailored bioprocess for pretreatment and saccharification of corn stalk into bioethanol using hydrolytic enzymes cocktail and fermentative yeasts - Manya Behl; Pushpak Dahiya; Deeksha Kumari; Kalpana Thakur; Mamta Devi; Ranju Kumari Rathour; Arvind Kumar Bhatt; Ravi Kant Bhatia (Biocatalysis and Agricultural Biotechnology, 2023)

In-situ synthesis of ionic liquid-based-carbon quantum dots as fluorescence probe for hemoglobin detection - Nisha Yadav; Deeksha Mudgal; Vivek Mishra (Analytica Chimica Acta, 2023)

Comparison of phenotypic and genotypic frequency of phosphine resistance in select field populations of Tribolium castaneum from India - M. G. Deeksha; Suresh M. Nebapure; Vinay Kumari Kalia; Doddachowdappa Sagar; Ramcharan Bhattacharya; Anil Dahuja; Sabtharishi Subramanian (Molecular Biology Reports, 2023)

Hazardous impacts of glyphosate on human and environment health: Occurrence and detection in food - Deeksha Rawat; Aarti Bains; Prince Chawla; Ravinder Kaushik; Rahul Yadav; Anil Kumar; Kandi Sridhar; Minaxi Sharma (Chemosphere, 2023)

Integrated fermentative production and downstream processing of L-malic acid by Aspergillus wentii using cassava peel waste - Deeksha Gopaliya; Saniya Zaidi; Nitin Srivastava; Bhumika Rani; Vinod Kumar; Sunil Kumar Khare (Bioresource Technology, 2023)

Characterization of fine particulate matter water-soluble inorganic ions and estimation of aerosol acidity at three COALESCE network sites — Mysuru, Bhopal, and Mesra — in India - Abisheg Dhandapani; Jawed Iqbal; Radhakrishnan Naresh Kumar; Ankur Bhardwaj; Deeksha Shukla; Ramya Sunder Raman; Sanyasihally Vasanthkumar Laxmi Prasad; Boohalli Mahadevappa Sadashiva Murthy (Environmental Science and Pollution Research, 2023)

Isolation and Chemical Structural Elucidation of Antibacterial Bioactive Compounds from Endophytic Fungal Strain Phoma sp. D1 - Suneel Kumar; Ravindra Prasad Aharwal; Deeksha Singh; Deepa Mishra; Ashish K. Sarangi; Ranjan K. Mohapatra; Ashwani Kumar Sharma; Sardul Singh Sandhu (Current Pharmacology Reports, 2023)

Recycling potential of brewer's spent grains for circular biorefineries - Deepti Agrawal; Deeksha Gopaliya; Nicholas Willoughby; Sunil K. Khare; Vinod Kumar (Current Opinion in Green and Sustainable Chemistry, 2023)

Electrophysiological and Behavioral Responses of Spotted Stem Borer, Chilo partellus, to Sex Pheromone Components and Their Blends - Niraj Guleria; Suresh M. Nebapure; P. D. Kamala Jayanthi; Suby S.B.; Deeksha MG (Journal of Chemical Ecology, 2023)

Functional genomic analysis of an efficient indole degrading bacteria strain Alcaligenes faecalis IITR89 and its biodegradation characteristics - Raj Kumar Regar; Deeksha Singh; Vivek Kumar Gaur; Ravindra Singh Thakur; Natesan Manickam (Environmental Science and Pollution Research, 2023)

BCL-2 protein family: attractive targets for cancer therapy - Deeksha Kaloni; Sarah T Diepstraten; Andreas Strasser; Gemma L Kelly (Apoptosis, 2023)
Acquired resistance to cell death is a hallmark of cancer. The BCL-2 protein family members play important roles in controlling apoptotic cell death. Abnormal over-expression of pro-survival BCL-2 family members or abnormal reduction of pro-apoptotic BCL-2 family proteins, both resulting in the inhibition of apoptosis, are frequently detected in diverse malignancies. The critical role of the pro-survival and pro-apoptotic BCL-2 family proteins in the regulation of apoptosis makes them attractive targets for the development of agents for the treatment of cancer. This review describes the roles of the various pro-survival and pro-apoptotic members of the BCL-2 protein family in normal development and organismal function and how defects in the control of apoptosis promote the development and therapy resistance of cancer. Finally, we discuss the development of inhibitors of pro-survival BCL-2 proteins, termed BH3-mimetic drugs, as novel agents for cancer therapy.

Crop classification by using dual-pol SAR vegetation indices derived from Sentinel-1 SAR-C data - Deeksha Mishra; Gunjan Pathak; Bhanu Pratap Singh; Mohit; Parveen Sihag; Rajeev; Kalyan Singh; Sultan Singh (Environmental Monitoring and Assessment, 2023)

Critical factors governing the efficient direct organogenesis in green-fleshed kiwifruit (Actinidia deliciosa) [A. Chev.] var. deliciosa - Deeksha Thakur; Parul Sharma; Rajnish Sharma; Chanchal Kumari; Vishal Singh Rana (In Vitro Cellular & Developmental Biology - Plant, 2022)

Polymer-Coated Polymeric (PCP) Microneedles for Controlled Dermal Delivery of 5-Fluorouracil - Anusha V. Matadh; Deeksha Jakka; S. G. Pragathi; Srinath Rangappa; H. N. Shivakumar; Howard Maibach; N. M. Reena; S. Narasimha Murthy (AAPS PharmSciTech, 2022)

Plant Quarantine Regulations With Reference to Sugarcane in India: Strengths and Challenges - S. N. Sushil; Deeksha Joshi; Sharmila Roy; G. P. Rao; A. D. Pathak (Sugar Tech, 2022)

Mass balance estimation of Mulkila glacier, Western Himalayas, using glacier melt model - Geetha Priya M.; Chandhana Guruprasad; Deeksha Gopal; Suresh Devaraj (Environmental Monitoring and Assessment, 2022)

Geospatial analysis of land degradation by fuzzy membership algorithm in reference to Satna river basin in northern foreland of Peninsular India - Narayan Datt Tiwari; Deeksha Mishra (Arabian Journal of Geosciences, 2022)

Plant- pollinator interaction network among the scrubland weed flora from foothills of north-western Indian Himalaya - M. G. Deeksha; Mohammad Sarfraz Khan; K. M. Kumaranag (International Journal of Tropical Insect Science, 2022)

Methylxanthines as Potential Inhibitor of SARS-CoV-2: an In Silico Approach - Rajan Rolta; Deeksha Salaria; Bhanu Sharma; Oladoja Awofisayo; Olatomide A. Fadare; Sonum Sharma; Chirag N. Patel; Vikas Kumar; Anuradha Sourirajan; David J. Baumler; Kamal Dev (Current Pharmacology Reports, 2022)

Analyzing the extent of drought in the Rajasthan state of India using vegetation condition index and standardized precipitation index - Deeksha Mishra; Suresh Goswami; Shafique Matin; Jyoti Sarup (Modeling Earth Systems and Environment, 2022)

Indoor Air Quality Monitoring of Urban and Rural Households of a North Indian City During Cooking Hours - Deeksha Shukla; Venkatesh Dutta (Aerosol Science and Engineering, 2022)

Seasonal incidence, epidemiology and establishment of different pests and disease in laboratory reared Bombus haemorrhoidalis Smith - Harish Kumar Sharma; Lalit Kalia; Ruchi Sharma; Meena Thakur; Hema Prasad; Manju Devi; Priyanka Thakur; Deeksha Sharma; Kiran Rana (International Journal of Tropical Insect Science, 2021)

Correction to: Bio‐control potential of Trichoderma spp., against Fusarium spp., the incitants of Pokkah boeng disease of sugarcane under in‐vitro conditions - Raghvendra Tiwari; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Deeksha Joshi; Kajal Chandra; Asha Gaur; Abhay Srivastava; Rajesh Kumar Tiwari (Indian Phytopathology, 2021)

A global comparison of implementation and effectiveness of materiovigilance program: overview of regulations - Deeksha Joshi; Ishita Sharma; Saurabh Gupta; Thakur Gurjeet Singh; Sonia Dhiman; Abhimanyu Prashar; Monica Gulati; Bimlesh Kumar; Sukriti Vishwas; Dinesh Kumar Chellappan; Gaurav Gupta; Niraj Kumar Jha; et al. (Environmental Science and Pollution Research, 2021)

Bio‐control potential of Trichoderma spp., against Fusarium spp., the incitants of Pokkah boeng disease of sugarcane under in‐vitro conditions - Raghvendra Tiwari; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Deeksha Joshi; Kajal Chandra; Asha Gaur; Abhay Srivastava; Rajesh Kumar Tiwari (Indian Phytopathology, 2021)

Exploring potential of different fungicides for management of red rot of sugarcane under sub-tropical India - Deeksha Joshi (Indian Phytopathology, 2021)

Management of Termites Through Different Tools and Their Impact on Environment and Soil Micro-arthropods in Sugarcane in Indo-Gangetic Plains of India - S. N. Sushil; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Phytocompounds of Rheum emodi, Thymus serpyllum, and Artemisia annua Inhibit Spike Protein of SARS-CoV-2 Binding to ACE2 Receptor: In Silico Approach - Rajan Rolta; Deeksha Salaria; PremPrakash Sharma; Bhanu Sharma; Vikas Kumar; Brijesh Rathi; Mansi Verma; Anuradha Sourirajan; David J. Baumler; Kamal Dev (Current Pharmacology Reports, 2021)

Pharmaceutical effluent: a critical link in the interconnected ecosystem promoting antimicrobial resistance - Anita Kotwani; Jyoti Joshi; Deeksha Kaloni (Environmental Science and Pollution Research, 2021)

Fiji Sugarcane Industry Amidst COVID-19 Pandemic - Hirdesh Kumar Sachan; Deeksha Krishna (Sugar Tech, 2021)

Fine Particulate Matter Bound Polycyclic Aromatic Hydrocarbons and Carbonaceous Species in Delhi’s Atmosphere: Seasonal Variation, Sources, and Health Risk Assessment - Amit Kumar Yadav; Sayantan Sarkar; Darpa Saurav Jyethi; Prashant Rawat; Deeksha Aithani; Zainab Siddiqui; P. S. Khillare (Aerosol Science and Engineering, 2021)

Biology, predatory potential and functional response of Mallada desjardinsi (Navas) on melon aphid, Aphis gossypii glover - Deeksha Kumari; Subhash Chander Verma; Prem Lal Sharma; Mahesh Balaso Gaikwad (International Journal of Tropical Insect Science, 2021)

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Role of Arabidopsis BBX proteins in light signaling - Arpita Yadav; Nevedha Ravindran; Deeksha Singh; Puthan Valappil Rahul; Sourav Datta (Journal of Plant Biochemistry and Biotechnology, 2020)

Removal of heavy metals and radionuclides from water using nanomaterials: current scenario and future prospects - Vinod Kumar; Deeksha Katyal; SwayangSiddha Nayak (Environmental Science and Pollution Research, 2020)

Pollution characteristics and human health risk from trace metals in roadside soil and road dust around major urban parks in Delhi city - Zainab Siddiqui; P. S. Khillare; Darpa Saurav Jyethi; Deeksha Aithani; Amit Kumar Yadav (Air Quality, Atmosphere & Health, 2020)

Effect of different inocula of Meloidogyne incognita and Pseudomonas syringae pv. pisi with and without Rhizobium leguminosarum on growth, chlorophyll, carotenoid and proline contents of pea - Deeksha Kashyap; Zaki A. Siddiqui (Indian Phytopathology, 2020)

Site Suitability Analysis of Solar Energy Plants in Stony Wasteland Area: A Case Study of Trans-Yamuna Upland Region, Allahabad District, India - Deeksha Mishra (Journal of the Indian Society of Remote Sensing, 2020)

Therapeutic Targets in Telomerase and Telomere Biology of Cancers - Rajendra Prasad; Deeksha Pal; Wajid Mohammad (Indian Journal of Clinical Biochemistry, 2020)

Novel thiazolinyl-picolinamide based palladium(II) complex-impregnated urinary catheters quench the virulence and disintegrate the biofilms of uropathogens - Deeksha Rajkumar; Durairajan Rubini; M. Sudharsan; D. Suresh; Paramasivam Nithyanand (Biofouling, 2020)

Prognostic role of 14q32.31 miRNA cluster in various carcinomas: a systematic review and meta-analysis - Padacherri Vethil Jishnu; Pradyumna Jayaram; Vaibhav Shukla; Vinay Koshy Varghese; Deeksha Pandey; Krishna Sharan; Sanjiban Chakrabarty; Kapaettu Satyamoorthy; Shama Prasada Kabekkodu (Clinical & Experimental Metastasis, 2020)

Distribution, Composition and Bioactivity of Endophytic Trichoderma spp. Associated with Sugarcane - Deeksha Joshi; Jaya Gupta; Ayushi Mishra; Monika Upadhyay; S. K. Holkar; Pushpa Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Identification of Groundwater Prospect in Bara Region of Allahabad District Based on Hydro-Geomorphological Analysis Using Satellite Imagery - Deeksha Mishra; B. N. Singh (Journal of the Indian Society of Remote Sensing, 2019)

Trichoderma-Mediated Suppression of Red Rot of Sugarcane Under Field Conditions in Subtropical India - Deeksha Joshi; Pushpa Singh; S. K. Holkar; Sanjeev Kumar (Sugar Tech, 2019)

Protection of Primary Dopaminergic Midbrain Neurons Through Impact of Small Molecules Using Virtual Screening of GPR139 Supported by Molecular Dynamic Simulation and Systems Biology - Aman Chandra Kaushik; Deeksha Gautam; Asma Sindhoo Nangraj; Dong-Qing Wei; Shakti Sahi (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Derivation of Magnitude of Crop Diversity Through NDVI Composite Index Using Sentinel-2 Satellite Imagery - Deeksha Mishra; B. N. Singh (Journal of the Indian Society of Remote Sensing, 2019)

Exploring Efficacious Microbial Bio-agents and Insecticides Against White Grubs in Sugarcane in Indo-Gangetic Plains - S. N. Sushil; Deeksha Joshi; G. M. Tripathi; M. R. Singh; Arun Baitha; D. C. Rajak; S. Solomon (Sugar Tech, 2018)

Spatial methane emission modelling from wetlands using geospatial tools - Sangeeta Bansal; J. K. Garg; C. S. Sharma; Deeksha Katyal (International Journal of Remote Sensing, 2018)

Trichoderma elicitors create a potential chemical barrier through induced systemic resistance against Colletotrichum falcatum and minimise sucrose losses in sugarcane - Pushpa Singh; Nidhi Tripathi; Deeksha Joshi; Ashwini Dutt Pathak; Arun Sethi (Journal of Plant Pathology, 2018)

Morphological and Biochemical Characteristics of Avian Faecal Droppings and Their Impact on Survival of Avian Influenza Virus - Shailesh D. Pawar; Satish A. Pande; Deeksha S. Tare; Sachin S. Keng; Sadhana S. Kode; Dinesh K. Singh; Jayati Mullick (Food and Environmental Virology, 2018)

Banded Leaf and Sheath Blight of Maize: Historical Perspectives, Current Status and Future Directions - K. S. Hooda; M. K. Khokhar; H. Parmar; Robin Gogoi; Deeksha Joshi; S. S. Sharma; O. P. Yadav (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Comprehensive assessment of the genes involved in withanolide biosynthesis from Withania somnifera: chemotype-specific and elicitor-responsive expression - Aditya Vikram Agarwal; Parul Gupta; Deeksha Singh; Yogeshwar Vikram Dhar; Deepak Chandra; Prabodh Kumar Trivedi (Functional & Integrative Genomics, 2017)

Sources of errors in the simulation of south Asian summer monsoon in the CMIP5 GCMs - Moetasim Ashfaq; Deeksha Rastogi; Rui Mei; Danielle Touma; L. Ruby Leung (Climate Dynamics, 2017)

Expression of Telomere Binding Proteins (RAP1 and POT1) in Renal Cell Carcinoma and Their Correlation with Clinicopathological Parameters - Deeksha Pal; Shrawan Kumar Singh; Nandita Kakkar; Rajendra Prasad (Indian Journal of Clinical Biochemistry, 2017)

Exogenous Application of Ethrel and Gibberellic Acid Stimulates Physiological Growth of Late Planted Sugarcane with Short Growth Period in Sub-tropical India - Rama Kant Rai; Nidhi Tripathi; Deeksha Gautam; Pushpa Singh (Journal of Plant Growth Regulation, 2017)

Antifungal Potential of Metabolites from Trichoderma sp. Against Colletotrichum falcatum Went Causing Red Rot of Sugarcane - Deeksha Joshi; Pushpa Singh; A. K. Singh; R. J. Lal; Nidhi Tripathi (Sugar Tech, 2016)

Alkaline Phosphatase: An Overview - Ujjawal Sharma; Deeksha Pal; Rajendra Prasad (Indian Journal of Clinical Biochemistry, 2014)

Characterization of Trichoderma Isolates from Sugarcane Agro-Ecosystem and their Efficacy Against Colletotrichum falcatum Causing Red Rot of Sugarcane - Deeksha Joshi; S. C. Misra (Sugar Tech, 2013)

Microbes to Generate Electricity - Deeksha Lal (Indian Journal of Microbiology, 2013)

Implication of BBM lipid composition and fluidity in mitigated alkaline phosphatase activity in renal cell carcinoma - Ujjawal Sharma; Shrawan Kumar Singh; Deeksha Pal; Ragini Khajuria; Arup Kumar Mandal; Rajendra Prasad (Molecular and Cellular Biochemistry, 2012)

Variability in Activities of Sucrose Metabolizing Enzymes in Relation to Sucrose Accumulation Among Parents and Their Progenies of Sugarcane - Suresh K. Batta; Deeksha; K. S. Thind; Pritpal Singh; S. K. Uppal (Sugar Tech, 2011)

Classification of Rice Seed Storage Proteins using Neural Networks - Soma Marla; Deeksha Bharatiya; Madhu Bala; Vinay Singh; Anil Kumar (Journal of Plant Biochemistry and Biotechnology, 2010)